Teleworking Transformation : Evaluating Post-Pandemic Impacts on Employees and Corporate Leadership. - Khachatrian, Karen (2023)
This thesis aims to explore the dynamics of teleworking, emphasizing a comparison between the pre-COVID and post-COVID periods. The study investigates both the positive and negative impacts of teleworking on employees and focuses on understanding the obstacles to teleworking adoption from a company leadership perspective. A mixed method approach was implemented including questionnaire with 100 employees of different European and American countries and five in-depth interviews of companys’ leaders. The findings of this research offer valuable insights for employees, corporate leaders, and policymakers navigating the evolving teleworking landscape. Recommendations and summaries are based on the results obtained from the conducted questionnaire and interviews.